Biomedical Applications of Bacterial Cellulose based Composite Hydrogels - Liu, Wei; Du, Haishun; Zheng, Ting; Si, Chuanling (Current Medicinal Chemistry, 2021)
Background: Bacterial cellulose (BC) and its derivatives are a rich source of renewable natural ingredients, which are of great significance for biomedical and medical applications but have not yet been fully exploited. BC is a high-purity, biocompatible, and versatile biomaterial that can be used alone or in combination with other ingredients such as polymers and nanoparticles to provide different structural organization and function. This review briefly introduces the research status of BC hydrogels, focusing on the preparation of BC-based composite hydrogels and their applications in the field of biomedicine, particularly the wound dressings, tissue engineering scaffolds, and drug delivery. Methods: By reviewing the most recent literature on this subject, we summarized recent advances in the preparation of BC-based composite hydrogels and their advances in biomedical applications, including wound dressings, tissue engineering, and drug delivery. Results: BC composite hydrogels have broadened the field of application of BC and developed a variety of BC-based biomaterials with excellent properties. BC-based hydrogels have good biocompatibility and broad application prospects in the biomedical field. Conclusion: BC-based composite hydrogels with the advantages of 3D structure, nontoxicity, high purity, and good biocompatibility, have great prospects in the development of sustainable and multifunctional biomaterials for biomedical applications.
Keywords: wound healing